SIMPLIFIED ANALYSIS OF HYSTERESIS DRY FRICTION VIBRATION ISOLATION SYSTEM ON FLEXIBLE FOUNDATION - WU RongPing; BAI HongBai; LU ChunHong (Jixie qiangdu)
In engineering practice,the non-linear vibration isolation systems are widely founded on the flexible foundation,and its application and research are seriously restricted to the analysis of vibration characteristic. First of all,basing on the hysteresis dry friction vibration isolation system which contains cubic nonlinear stiffness,a kinetic equation is derived by means of vibration separation method. Combing with the incremental harmonic balance method,the response of the system are obtained in the case that the flexible plate undergoes any order of main vibrations. Then,the formula of force transfer rate of the system is deduced basing on the fundamental harmonics term,and the influences of the parameters of the vibration isolator on the force transfer rate of the system are analyzed qualitatively according to the formula. It is found that the reduction of the stiffness coefficient,the increase of the damping coefficient and the increase of the static friction limit can effectively reduce the force transfer rate of the system. The research provides a reliable reference for the practical application of the system.